2014
DOI: 10.1016/j.radonc.2014.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Impact of radiotherapy boost on pathological complete response in patients with locally advanced rectal cancer: A systematic review and meta-analysis

Abstract: Dose escalation above 60 Gy for locally advanced rectal cancer results in high pCR-rates and acceptable early toxicity. This observation needs to be further investigated within larger randomized controlled phase 3 trials in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
93
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 78 publications
10
93
0
2
Order By: Relevance
“…In the present study, 91.8% of eligible patients received IMRT with boost irradiation to primary tumor of 55Gy in 25 fractions. The pCR rate was 21.4%, which was consistent with the previous meta-analysis [23]. Another propensity-score matching analysis [21] reported that the pCR rate wasn't significantly different between elderly and younger patients (14.8% vs 17.1%, P=0.433).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the present study, 91.8% of eligible patients received IMRT with boost irradiation to primary tumor of 55Gy in 25 fractions. The pCR rate was 21.4%, which was consistent with the previous meta-analysis [23]. Another propensity-score matching analysis [21] reported that the pCR rate wasn't significantly different between elderly and younger patients (14.8% vs 17.1%, P=0.433).…”
Section: Discussionsupporting
confidence: 86%
“…The pCR rate is significantly influenced by the escalated dose to primary tumor. When receiving ≥60 Gy irradiation, the pooled pCR rate was 20.4% in a mata-analysis [23]. A prospective study from China recruited 63 patients with LARC, patients received IMRT with pelvic to 41.8Gy in 22 fractions and primary tumor to 50.6Gy simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The use of progressively higher doses naturally raises concerns regarding treatment toxicity; however, a recent meta-analysis of 14 studies including 487 patients with locally advanced rectal cancer, all treated with doses of ≥6000 cGy, demonstrated acceptable early toxicity, with a pCR rate of 20.4 % and a pooled estimate of 10.3 % for grade 3 or higher toxicity. 34 The application of intensity-modulated radiation therapy (IMRT), while not yet standard treatment, may help to reduce this toxicity further without compromising response rates. 25,33,48–50 Similar to previous studies, we did not identify a lower likelihood of pCR in patients who received IMRT relative to standard external beam therapy.…”
Section: Discussionmentioning
confidence: 99%
“…surgery) or to treatment intensification (e.g. dose escalation or addition of targeted agents) [62]. Some authors found that a low pretreatment ADC was correlated with a good response to treatment.…”
Section: Discussionmentioning
confidence: 99%